1979
DOI: 10.1021/ic50192a019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and reactivity of coordinated sulfenic acids

Abstract: Several bis(ethylenediamine)cobalt(III) complexes containing chelated, S-bonded sulfenic acid ligands have been synthesized and characterized. [(en)2Co(S(0)CH2CH2NH2)]2+ and [(en)2Co(S(0)CH2COO)]+ are prototypes of this class of complexes. The general preparative route to sulfenato complexes involves stoichiometric oxidation of the corresponding thiolato complex with a 2-equiv oxidant, e.g., H202, in aqueous solution. Subsequent oxidation converts the sulfenato complex to the corresponding sulfinato complex. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
51
0
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 12 publications
(18 reference statements)
12
51
0
1
Order By: Relevance
“…27,39,68,[70][71][72][73][74] DFT calculations described earlier indicated that the S-O bond of 5 is single and significantly polarized. This is supported by the X-ray structure.…”
Section: Structural and Reactivity Properties Of The Metal-bound Sulfmentioning
confidence: 90%
“…27,39,68,[70][71][72][73][74] DFT calculations described earlier indicated that the S-O bond of 5 is single and significantly polarized. This is supported by the X-ray structure.…”
Section: Structural and Reactivity Properties Of The Metal-bound Sulfmentioning
confidence: 90%
“…These signals are within the range expected for S-bonded sulfone. [35][36][37] The SdO stretching vibration of diphenyl sulfone, Ph-SO 2 - Ph, is present at 1165 cm -1 . 35 These results confirm both the sulfonation of PEEK and the cross-linking.…”
Section: Atr/ftir Study Of Membranesmentioning
confidence: 99%
“…Early studies on sulfenato ligands in cobalt complexes demonstrated the nucleophilicity of the sulfenato oxygen (9,10), and recently, this same characteristic was observed in NHases wherein the sulfenato oxygen reacted with electrophilic boronic acids (11). Quite tellingly, the activities of NHase, the related thiocyanate hydrolase, and NHase mimics were found to depend on the presence of these sulfenato ligands where oxidation to the sulfinate abrogated activity (12)(13)(14).…”
Section: Nitrile Hydratases (Nhases)mentioning
confidence: 79%